INTEGRATED NUTRIENT MANAGEMENT IN WHEAT (TRITICUM AESTIVUM) - SINGH, R.K; AGARWAL, R.L.; Singh, SANDIP K. (Annals of Agricultural Research, 2014)
Field experiment was conducted at Research Farm of R.B.S. College, Bichpuri, Agra during rabi season of 2000-01 and 2001-02, with eleven treatments viz., control, Azotobacter, Azospirillum, FYM @ 5 t/ha, 50 kg N/ha, 100 kg N/ha, 150 kg N/ha , 50 kg N/ha + Azotobacter, 50 kg N/ha + Azospirillum, 50 kg N/ha + Azotobacter + FYM @ 5 t/ha and 50 kg N/ha + Azospirillum + FYM @ 5 t/ha. Results revealed that the application of 150 kg N/ha may be replaced by the various combination of biofertilizers, FYM and chemical fertilizes which will be more remunerative in terms of low input cost and sustainable productivity and soil health for longer period.